2019
DOI: 10.1136/jnnp-2018-319927
|View full text |Cite
|
Sign up to set email alerts
|

Current epidemiology of cerebrospinal fluid shunt surgery in the UK and Ireland (2004–2013)

Abstract: ObjectivesTo determine current epidemiology and clinical characteristics of cerebrospinal fluid (CSF) shunt surgery, including revisions.MethodsA retrospective, multicentre, registry-based study was conducted based on 10 years’ data from the UK Shunt Registry, including primary and revision shunting procedures reported between 2004 and 2013. Incidence rates of primary shunts, descriptive statistics and shunt revision rates were calculated stratified by age group, geographical region and year of operation.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Overall infection rates have commonly been reported to be around 5–6% in adult patients [ 12 , 17 , 19 ] but also significantly higher (8–15%) [ 13 ]. In a recent epidemiological study, the infection rate was reported to be around 12% [ 5 ]. In the current study, the infection was the most common cause for the first revision.…”
Section: Discussionmentioning
confidence: 99%
“…Overall infection rates have commonly been reported to be around 5–6% in adult patients [ 12 , 17 , 19 ] but also significantly higher (8–15%) [ 13 ]. In a recent epidemiological study, the infection rate was reported to be around 12% [ 5 ]. In the current study, the infection was the most common cause for the first revision.…”
Section: Discussionmentioning
confidence: 99%
“…The risk varies significantly with surgical procedure, duration and whether devices are implanted ( Kourbeti et al , 2015 ). The most common implanted devices are either temporary external ventricular drains (EVD) or permanent ventriculoperitoneal (VP) shunts for controlling hydrocephalus ( Fernández-Méndez et al , 2019 ). Both EVD and VP shunt insertion carry a significant risk of infection, with recent large UK prospective studies showing rates of 9.3% in 495 EVD insertions ( Jamjoom et al , 2018 ) and 6% in 1594 first VP shunts ( Mallucci et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A positive response to the withdrawal of CSF has been reported to have a positive predictive value in the range of 73-100% [20][21][22]. In addition, VPS has well-known complications, such as wound healing problems, bleeding, malfunction, and infections [23,24]. It was also reported that when CP and VPS placement were performed simultaneously, the complication rate was higher than that of staged surgery [11,25].…”
Section: Discussionmentioning
confidence: 99%